2022
DOI: 10.3390/molecules27020446
|View full text |Cite
|
Sign up to set email alerts
|

Options to Improve the Mechanical Properties of Protein-Based Materials

Abstract: While bio-based but chemically synthesized polymers such as polylactic acid require industrial conditions for biodegradation, protein-based materials are home compostable and show high potential for disposable products that are not collected. However, so far, such materials lack in their mechanical properties to reach the requirements for, e.g., packaging applications. Relevant measures for such a modification of protein-based materials are plasticization and cross-linking; the former increasing the elasticity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 96 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…In line with calorimetric results, these results indicate that cardiac plasticization is caused by an extracellular phenomenon independent of intracellular cholesterol levels, in contrast to the other biophysical alterations in the ECM components. Due to their amphiphilic character, biomacromolecules are also known to interact with lipids via hydrophobic association, and lipids can act as efficient plasticizers. , Previous studies from our group have shown that aggregated LDL favors a softness of tropoelastin . In addition, CE-enriched lipoproteins per se have been reported to produce an increase in the free volume of ECM macromolecules, causing a swelling and plasticization of the tissues. , In line, the reduction of circulating levels of CE-enriched lipoprotein levels improved arterial stiffness in humans .…”
Section: Results and Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In line with calorimetric results, these results indicate that cardiac plasticization is caused by an extracellular phenomenon independent of intracellular cholesterol levels, in contrast to the other biophysical alterations in the ECM components. Due to their amphiphilic character, biomacromolecules are also known to interact with lipids via hydrophobic association, and lipids can act as efficient plasticizers. , Previous studies from our group have shown that aggregated LDL favors a softness of tropoelastin . In addition, CE-enriched lipoproteins per se have been reported to produce an increase in the free volume of ECM macromolecules, causing a swelling and plasticization of the tissues. , In line, the reduction of circulating levels of CE-enriched lipoprotein levels improved arterial stiffness in humans .…”
Section: Results and Discussionmentioning
confidence: 63%
“…Due to their amphiphilic character, biomacromolecules are also known to interact with lipids via hydrophobic association, and lipids can act as efficient plasticizers. 63,65 Previous studies from our group have shown that aggregated LDL favors a softness of tropoelastin. 25 In addition, CE-enriched lipoproteins per se have been reported to produce an increase in the free volume of ECM macromolecules, causing a swelling and plasticization of the tissues.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this study, no cross-linking agent was used in the HA/gelatine bio composite mixture. Crosslinking agents play a role in connecting molecular chains in bio composite materials so that later they can form strong cross-links and increase the strength and stiffness of the material ( [42], [43]). Adding a cross-linking agent to the HA/gelatine bio composite solution also reduces the tendency for melting or deformation when passing through the nozzle [44].…”
Section: Extrusion Resultsmentioning
confidence: 99%
“…All proteins have complex polymeric structures; however, they are not structurally stable by nature. Using different strategies, the mechanical characteristics of protein-based films can be enhanced, such as by introducing a plasticizer into the protein matrix [ 59 ]. Different animal-based proteins including gelatin, casein, and whey protein are utilized in forming edible films due to their significant film-forming characteristics, such as mechanical and barrier characteristics.…”
Section: Mechanical Properties Of Animal-based Proteinmentioning
confidence: 99%